مجلة دراسات في التاريخ والاثار 71: نصوص مسمارية غير منشورة من العصر البابلي القديم في المتحف العراقي - رضا حسين محمد (مجلة دراسات في التاريخ والآثار, 2020)
Abstract: The economic texts represent most of the cuneiform texts discovered in Mesopotamia. Its importance is providing great information about the economy of each city. In the Old Babylonian period (2000-1595 B.C), economic activity flourished